Comparative financial performance between Islamic and conventional banks / Nuruhida Kamar - Kamar, Nuruhida (2008)
Nowadays, Islamic banks getting more attracted rather than non Islamic banks in Malaysia. The study will do the comparison the financial performance of the Islamic banks and conventional banks in Malaysia. It will cover two Islamic banks and three conventional banks in Malaysia. This will do by analyzing the performance and determinants of efficiency and profitability of Islamic and conventional banks. Financial ratios are applied in measuring the performances. The analysis of bank performance concentrates on four financial ratios which are profitability, liquidity, risk and solvency and efficiency. The study found that Islamic banks are relatively more profitability, less liquid, less risky and more efficient compared than conventional banks. The comparison of financial measures expressed in terms of various financial ratios indicates that there are no major differences in profitability, liquidity, risk and solvency and efficiency ratio between Islamic and conventional banks. The findings also indicate that Islamic banks as newcomers to the financial market are doing as well as conventional banks.